Dry early Holocene revealed by sand dune accumulation chronology in Bayanbulak Basin (Xinjiang, NW China). (May 2014) - Long, Hao; Shen, Ji; Tsukamoto, Sumiko; Chen, Jianhui; Yang, Linhai; Frechen, Manfred
Understanding the Holocene climate changes (especially moisture variation) and their mechanisms in the semiarid–arid Central Asia (SCA) is very important, as water availability is crucial for sustainable developments in this area. This study presents chronostratigraphy of an aeolian sedimentary sequence from Bayanbulak Basin (Xinjiang, NW China), aiming to infer the Holocene moisture history in the SCA. Luminescence dating technique was selected to construct the age framework of the study section. Since the luminescence signal intensity of quartz from the samples was too low to be detected, feldspar was used as an alternative dosimeter. A newly developed post-infrared (IR) IR-stimulated luminescence (IRSL) (pIRIR) dating protocol on K-feldspar was applied to determine the ages of samples. A set of tests on luminescence characteristics was performed and demonstrate that this method is suitable and the resultant ages are reliable. Combined with the stratigraphic investigation on the sand dune/palaeosol section, the results imply a very dry climatic condition characterized by sand dune accumulation at ~9–8 kyr, and a wet interval of 5–1.6 kyr when a soil layer was formed. This moisture variation pattern is consistent with that inferred from many lacustrine records in the SCA, suggesting a widespread dry period at 11–8 kyr. The present results appear to challenge a new stalagmite δ 18 O sequence, located nearby to Bayanbulak Basin, which instead suggested a humid early Holocene.